2018
DOI: 10.1186/s40425-018-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy for nodal metastasis in NSCLC with acquired resistance to immunotherapy

Abstract: Novel approaches with checkpoint inhibitors in immunotherapy continue to be essential in the treatment of non-small cell lung cancer (NSCLC). However, the low rate of primary response and the development of acquired resistance during the immunotherapy limit their long-term effectiveness. The underlying cause of acquired resistance is poorly understood; potential management strategies for patients with acquired resistance are even less clear. Here, we report the case of a 75-year-old female smoker with cough, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Gettinger et al reported that 11 NSCLC patients continued immunotherapy beyond AR 13 . Adam LC et al reported an AR case of successful local control with cryotherapy combined with immunotherapy beyond progression 23 . Further analysis will help to define the clinical benefit for NSCLC patients with a durable response treated with ICI beyond progression.…”
Section: Discussionmentioning
confidence: 99%
“…Gettinger et al reported that 11 NSCLC patients continued immunotherapy beyond AR 13 . Adam LC et al reported an AR case of successful local control with cryotherapy combined with immunotherapy beyond progression 23 . Further analysis will help to define the clinical benefit for NSCLC patients with a durable response treated with ICI beyond progression.…”
Section: Discussionmentioning
confidence: 99%
“…3 In order to prevent NSCLC metastasis to prolong the survival of patients, several approaches have been proposed, such as traditional Chinese medicine therapy, the development of new compounds, chemo-immunotherapy, etc. [4][5][6] Among them, the chemo-immunotherapy combinations will become the first-line treatment for NSCLC, which significantly improved the progression-free survival (PFS) and overall survival (OS) rates of these patients. First-line chemoimmunotherapy combinations are starting to and will certainly revolutionize the current paradigm of metastatic NSCLC treatment because of their superior performance in PFS and OS, compared to the based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent response to PD-1 blockade despite negative PD-L1 status could be due to numerous mechanisms. Cryoablation has been suggested to sensitize tumors to immunotherapy [ 7 , 8 ]. In one proposed mechanism, tumor antigens released after cryoablation are taken up by antigen-presenting cells, which mature and induce tumor-specific T-cell activation and proliferation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%